SPECIFICITY OF ECOLOGICAL AUDIT OF BURIAL PLACES AND STORAGES OF RADIOACTIVE WASTES ON THE EXAMPLE OF CHNPP - Biliavskiy, George O.; Osadchuk, Yulia K.; Matviyenko, Olga Yu. (Proceedings of National Aviation University (archive), 2008)
The specificity of ecological audit of burial places and storages of radioactive wastes on the example of CHNPP is considered; namely main principles, positions, requirements, tasks, objects, subjects of ecological audit, a team of specialists for its fulfillment, ecological problems, connected with storing of radioactive wastes and their influence on the human’s health. Main possibilities of improving radioactive wastes control system are also considered.